Elicitive Conflict Transformation and New Media: In Search for a Common Ground - Suetzl, Wolfgang (2016)
Advocates of elicitive conflict transformation (ECT) maintain that the parties to a conflict are the most important resource in efforts to render that conflict less violent. According to them, the transformation of the conflict is immanent to the conflict itself. The claim of ECT theorists is that classical conflict resolution has mostly aimed at overcoming a conflict by means of neutral mediation, while conflict transformation is not primarily concerned with terminating a conflict and considers the conflict worker as part of the conflict system. Although ECT is a communication-based model of conflict management and relies on human media, its media-theoretical aspects are not made explicit, raising the question of what role technological media play in the communicative processes that make up ECT techniques. Through an examination of the claimed differences between conflict resolution and conflict transformation, and focusing on the common roots of new media and the elicitive model in systems and cybernetic theory, this paper asks whether any peacebuilding potential of new media could be found in a specific anti-propagandistic quality of distributed technological media. It concludes by looking at any such potential in social media.